MYELOID SARCOMA PRESENTING AS SKIN NODULES IN SULAYMANIYAH CITY - Delawer, Kani; Getta, Hisham Arif; Muheadeen, Dana N. (Journal of Sulaimani Medical College, 2025)
Myeloid sarcoma is a rare malignant myeloid tumour known as granulocytic sarcoma or chloroma. As not all myeloid leukaemias are derived from granulocytes, the preferred term is myeloid sarcoma instead of granulocytic sarcoma and chloroma, consisting of the myeloid blast with or without maturation. Myeloid sarcoma may occur de novo or precede or be associated with acute or chronic myeloid leukaemias, or represent a blast transformation of myeloproliferative disorders, myelodysplastic syndromes, or it may represent a relapsed state in patients diagnosed previously as AML regardless of blood or BM fi ndings. It is more common in adults between 45 and 55 years of age. Myeloid sarcoma can involve any body site other than the bone marrow that totally or partially effaced the tissue architecture. The most affected sites are lymph nodes, skin, and bones (1). Skin, soft tissues, bone, lymph nodes, GIT, and testis are common sites to be involved (2). Occurrence in the other sites like skull bones, orbit, and paranasal sinuses is unusual (3). The pathogenesis of this sarcoma is believed to be an aberrant expression of homing signals for the leukemic blasts on extramedullary sites compared to bone marrow.
Keywords: Myeloid sarcoma; Skin nodule; AML